Traditional Uses, Biological Activities, and Phytochemical Profile of Keji Beling (Strobilanthes crispus) Leaf Extract: A Review - Sukendi, Yeli; Rafi, Mohamad; Silviani, Dea; Wahyuni, Wulan Tri (Tropical Biopharmaca Research Center, IPB University, 2025)
Health treatment in Indonesia is diverse, encompassing both modern medicines using synthetic drugs and traditional practices relying on herbal plants. Traditional medicine is often preferred due to its lower cost and perceived lack of side effects. Keji beling (Strobilanthes crispus) is one such herb with potential medicinal properties. This article summarizes information regarding traditional uses, biological activities, phytochemical profiles, and active compounds of keji beling leaf extract. Traditionally, keji beling leaves are consumed as tea. The plant has demonstrated antioxidant, anti-diabetic, anticancer, antitumor, and antibacterial properties. These biological effects are attributed to its phytochemical constituents, including flavonoids, alkaloids, saponins, tannins, and terpenoids. Specific bioactive compounds in keji beling leaf extract comprise silicic acid, polyphenols, glycosides, catechins, rutin, epicatechin, myricetin, luteolin, apigenin, naringenin, and kaempferol.